Pengaruh CRM Terhadap Customer Loyalty dengan Customer Trust Sebagai Variabel Mediasi Pada Online Shop - Tyas Pratiwi Eka Sari; Kurniawati (Jurnal Manajemen, 2022)
The purpose of the study is to find out the influence of Customer Relationship Management (CRM) components, namely Customer Engagement, Customer Knowledge, Customer Advocacy, Customer Orientation and with Customer Loyalty, besides that this research also wants to look at the influence of Customer Trust mediating the influence of Customer Knowledge with Customer Loyalty in the Online Shop. This research is by the method of purposive samplings and non-probability samplings. The use of the data being tested is a data that comes from 261 questionnaires and that meets the criteria for having shopped through an online shop, the number is 259 respondents. By using the Likert And Amos 23 Scale as a tool to perform testing. The results showed that Customer Advocacy, Customer Engagement and Customer Trust were proven to have an effect on Customer Loyalty. In addition, this study shows the results if Customer Knowledge is proven to have an impact on Customer Trust. The limitations of researchers are only to examine the influence of CRM Online Shop only and this study did not examine on offline shops. So in the next research, it is hoped that it will be able to expand the object of research not only the Online Shop but also research the Offline Shop as well and the mediation variables Customer Trust can be replaced into Customer Satisfaction. The novelty of this study was tested for originality with several previously published studies, namely the Customer Trust variable being a mediation variable, and in this study focused on the Online Shop. Keyword: Customer Relationship Management; Customer Orientation; Loyalt;, Advocacy; Knowledge; Engangement; dan Trust.